Pastoral adaptation and policy environment: How discourses shape knowledge, policy and adaptation - Crane, Todd A.; Meunier, Julien (2018)
The purpose of this paper is to analyze how the policy environment in Senegal influences pastoral climate change adaptation. The analysis of the link between policy environment and pastoral adaptation is based on a case study in the Ngnith municipality of the Senegal River delta and other localities in the delta. We argue that past policies have both changed the ecological and social systems and also changed the viability of livelihoods, especially by integrating national and international markets supported by national policies and leading to land competition, increasing the pastoral vulnerability. The present policy environment shapes the pastoral adaptation because policy processes lead to new power relations that marginalized pastoralists. Changes in the stakeholders and their uneven distribution of power leads to inequalities in terms of land allocation opportunities and limitation of the flexible livelihoods access which is primordial of pastoralism resilience. In conclusion, we argue that unpacking the political dimension of social-environment interactions is helpful in understanding the evolution of pastoralists’ capacity to adapt to climate change.